2018
DOI: 10.3390/ijerph15020252
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Self-Reported Health Effects and Annoyance in Relation to Air Pollution Exposure in an Industrial Area in Eastern-Estonia

Abstract: Eastern Estonia has large oil shale mines and industrial facilities mainly focused on electricity generation from oil shale and shale oil extraction, which produce high air pollution emissions. The “Study of the health impact of the oil shale sector—SOHOS” was aimed at identifying the impacts on residents’ health and annoyance due to the industrial processing. First, a population-wide survey about health effects and annoyance was carried out. Second, the total and oil shale sectors’ emitted concentrations of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…If we take a look at the public health status of the population in Ida-Viru County, it is in many ways worse than in the rest of the country (e.g., life expectancy is four years lower than in the capital area) [15,16,79,80]. Several studies [79,81] have indicated that lower education could be an obstruction to better health-related behavioural choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If we take a look at the public health status of the population in Ida-Viru County, it is in many ways worse than in the rest of the country (e.g., life expectancy is four years lower than in the capital area) [15,16,79,80]. Several studies [79,81] have indicated that lower education could be an obstruction to better health-related behavioural choices.…”
Section: Discussionmentioning
confidence: 99%
“…Although the environmental quality in the region has improved, and the volumes of excavation are still lower than in the 1980s, the health impacts remain [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent published papers related to epidemiological studies in the industrial area has been taken and reviewed its background and objectives, data collection methods, and measures taken to analyse the collected data. Articles that have been reviewed in this section performs statistical regression analysis with evaluation measures, an odds ratio and a confidence interval (95%) to identify the association between risk factors and related diseases [7]- [13]. A combination of questionnaire study and air pollution exposure assessment using a dispersion model were used as materials for epidemiological studies that associates air pollution caused by industries and related health issues of individuals living in the proximity of it in [7]- [9], [11], [13].…”
Section: Literature On Epidemiological Studies In Industrial Areamentioning
confidence: 99%
“…Ambient air quality affects health, as toxic substances entering the respiratory tract can also reach other organs through the bloodstream, and cause various health problems and diseases (3). Health effects, related to the oil shale sector, have been studied in Estonia; studies suggest poorer health indicators, including increased respiratory and cardiovascular disease prevalence and a decrease in life expectancy (4). In addition, children living in the area have a higher risk of developing asthma (5,6).…”
Section: Introductionmentioning
confidence: 99%